Sex Differences in Rhythmic Preferences in the Budgerigar (Melopsittacus undulatus): A Comparative Study with Humans - Hoeschele, Marisa; Bowling, Daniel L. (Frontiers in Psychology, 2016)
A variety of parrot species have recently gained attention as members of a small group of non-human animals that are capable of coordinating their movements in time with a rhythmic pulse. This capacity is highly developed in humans, who display unparalleled sensitivity to musical beats and appear to prefer rhythmically organized sounds in their music. Do parrots also exhibit a preference for rhythmic over arrhythmic sounds? Here we presented humans and budgerigars (Melopsittacus undulatus) – a small parrot species that have been shown to be able to align movements with a beat – with rhythmic and arrhythmic sound patterns in an acoustic place preference paradigm. Both species were allowed to explore an environment for 5 minutes. We quantified how much time they spent in proximity to rhythmic vs. arrhythmic stimuli. The results show that humans spent more time with rhythmic stimuli, and also preferred rhythmic stimuli when directly asked in a post-test survey. Budgerigars did not show any such overall preferences. However, further examination of the budgerigar results showed an effect of sex, such that male budgerigars spent more time with arrthymic stimuli, and female budgerigars spent more time with rhythmic stimuli. Our results support the idea that rhythmic information is interesting to budgerigars. We suggest that future investigations into the temporal characteristics of naturalistic social behaviors in budgerigars, such as courtship vocalizations and head-bobbing displays, may help explain the sex difference we observed.